Research on cultivated land extraction based on MODIS NDVI time series matching analysis - WANG Hong-shuo; HUANG Jing-feng; XU Jun-feng; PENG Dai-liang (浙江大学学报. 农业与生命科学版)
MODIS NDVI data and time series matching method were used to extract the area of cultivated land with similar phenology. Time series of sample pixels from cultivated land were selected as standard time series spectrum, and the others were treated as testing time series spectrum to fix cultivated land according to t-test of matching coefficient. When matching position m=0, the matching accuracy at 10% t test level, with the correlation coefficient 0.60, was the highest of all levels; while the matching accuracy got from unsupervised classification of RMSE appraisal map, with higher correlation coefficient 0.79, was better than that of t-test method. The results indicate that cultivated land information extraction based on time series matching method was feasible and the matching accuracy could be used to reflect the consistent information about the phenologies of crop in study area.